Fibronectin-Grafted Titanium Dental Implants: An In Vivo Study. (6th June 2016) - Chang, Yu-Chi; Ho, Kuo-Ning; Feng, Sheng-Wei; Huang, Haw-Ming; Chang, Chia-Hsun; Lin, Che-Tong; Teng, Nai-Chia; Pan, Yu Hwa; Chang, Wei-Jen
Abstract : Modification of the physiochemical properties of titanium surfaces using glow discharge plasma (GDP) and fibronectin coating has been shown to enhance the surface hydrophilicity, surface roughness, cell adhesion, migration, and proliferation. This in vivo study aimed to evaluate the bone integration efficacy of a biologically modified implant surface. Two different surface-modified implants (Ar-GDP and GDP-fib) were placed in the mandibular premolar area of six beagle dogs for 2–8 weeks. Three techniques [histologic evaluation, resonance frequency analysis (RFA), and microcomputed tomography (micro-CT) evaluation] were used to detect the implant stability and bone-implant contact. The implant stability quotient values of GDP-fib implants were significantly greater than the Ar-GDP implants at 2 and 4 weeks (P < 0.01 ). The bone volume/total volume ratio of GDP-fib implants was greater than the Ar-GDP implants in micro-CT evaluation. A high positive correlation was observed between RFA and micro-CT measurements. At 2 weeks, osteoblasts were seen to line the implant surface, and multinuclear osteoclasts could be seen on the surface of old parent bone. After 8 weeks, a majority of the space in the wound chamber appeared to be replaced by bone. Enhancement of the stability of biologically modified implants was proved by the results of RFA, micro-CT, and histological analysis. This enhanced stability may help fasten treatment and be clinically beneficial.